O gerenciamento por categorias percebido pelo cliente: um estudo em uma rede de supermercados de Belo Horizonte - Luiz Antonio de Carvalho Godinho (2016)
Despite its economic crisis, the supermarket sector still accounts for 5.4% of the Brazilian GDP (ABRAS, 2016), with a large number of players of varying sizes who have been investing regularly in actions not only to get rid of the problems but also to stand out in their respective merchants. One of the actions implemented by the industry is Category Management (CG), a management tool related to efficient product assortment, one of the pillars of ECR (Efficient Consumer Response) that is based on delivering products to customers in the right time, availability and location (ECR, 2007). However, a scale developed to measure GC more broadly was not observed in the relevant literature. In addition, the GC is a way to increase the perception of value by the customers of the establishments that implement CDR (2014), highlighting these companies in their markets of operation. The overall objective of this paper was to examine the relationships between customer-perceived category management, brand reputation, perceived value, and trust in order to foster and explain customer satisfaction, commitment and loyalty to a BH supermarket. In order to achieve this end, it was first raised if GC could be perceived by clients (Perceived Categories Management - GCP) as a multidimensional construct.Subsequently, a measurement scale was developed for the management by categories perceived by the client. Third, the scales of the other constructs involved in the research were adequate for the reality of the consumers of the supermarket searched; Then, the relationship of GCP with customer perceived value was verified from a relationship marketing perspective and, finally, the model proposed here was tested and validated. For the qualitative steps, bibliographical research was carried out in the pertinent literature, as well as an on-line panel with specialists, in-depth interviews with store clients, and two discussion groups. At the end of each discussion group, what was called the Face Value Table (QFV) was implemented. At all stages of the qualitative phase, the data were analyzed through content analysis. For the quantitative phase, a survey was carried out with clients of the aforementioned supermarket. The quantitative data were analyzed based on Structural Equation Modeling using the Partial Least Squares (PLS) technique. The two phases were interdependent, and the qualitative step contributed strongly to the quantitative stage. After the analysis of the data, all the research hypotheses were confirmed, highlighting the strong influence that GCP has on the value perceived by the client. In addition, it is emphasized the creation of a scale for measuring GCP as a multidimensional construct. New indicators of impairment were also evident, in addition to those already traditionally addressed by Morgan and Hunt (1994). A characteristic of the sector pointed by the research was the low commitment of the clients with the supermarket searched. It was verified the need of the market study for each store that intends to implement the GC, in order to correctly segment its target audience. Finally, how supermarket managers need to implement GCP as a tool to aid decision making, since it generates value for customers. Management recommendations were also made with the intention of making GC a differential for those who use it.